Sistem Pendukung Keputusan Pemilihan Pelayanan Marketplace Menggunakan Metode Moora - Ade Winarni; Linda Apriyanti; Fozimat Amhas (Prosiding, 2022)
With the marketplace, buying and selling activities are easier to do, buyers do not need to come to the store, only with a smartphone. In this study, there is a problem where consumers have received unsatisfactory service when shopping at the marketplace and also there is no system that can determine the best marketplace in terms of service. In addition, service providers also need to know consumer ratings of their marketplace in order to improve services in the future. Therefore, a decision support system is built that can determine the best marketplace in terms of service. The criteria used in this study are overpayment or underpayment (transfer), order cancellation, chat response, return of goods or funds and tracking of orders obtained through distributing questionnaires to 40 respondents who have shopped in the marketplace. The approach used in this research is to use the MOORA method (Multi-objective optimization on the basis of ratio analysis). The system built with the Laravel Framework and using the MySQL database expected to be considered or a tool for prospective consumers to making decisions, as input to the marketplace to be able to improve its services and as information to the public, especially consumers regarding the ranking of the marketplace with the best service